Solar photoelectrochemical synthesis of electrolyte-free H2O2 aqueous solution without needing electrical bias and H2. Issue 5 (1st April 2021) - Jeon, Tae Hwa; Kim, Bupmo; Kim, Chuhyung; Xia, Chuan; Wang, Haotian; Alvarez, Pedro J. J.; Choi, Wonyong
Abstract : An external bias-free photoelectrochemical system containing solid polymer electrolytes achieves efficient and durable synthesis of pure (electrolyte-free) aqueous H2 O2 solution. Abstract : The conventional synthesis of hydrogen peroxide (H2 O2 ) such as heterogeneous catalytic and electrochemical processes requires H2 and O2 as reagents, costly noble metals, and organic solvents, which are energy/waste-intensive and hazardous. An alternative method of photoelectrochemical (PEC) synthesis that needs only water and sunlight is environment-friendly but its practical application is limited due to the energy-demanding method for the separation of the synthesized H2 O2 from the electrolytes. Herein, we demonstrated the direct synthesis of an electrolyte-free aqueous solution of pure H2 O2 by developing a PEC system with solid polymer electrolyte (SPE) and engineered electrodes. Ruthenium catalyst-decorated TiO2 nanorods (RuO x /TNR: photoanode) and anthraquinone-anchored graphite rods (AQ/G: cathode) are placed in an anode compartment and a cathode compartment, respectively, while a middle compartment containing SPE is located between these compartments. Upon solar simulating irradiation (AM 1.5G, 100 mW cm −2 ), the photoanode generates H + ions via water oxidation reaction (WOR) and the cathode generates HO2 − ions via two-electron oxygen reduction reaction (ORR), while the SPE selectively transports H + and HO2 − into the middle compartment to form pure H2 O2 solution. The combined system enabled continuous H2 O2 synthesis over 100 h even under bias-free (0.0 V of cell voltage) conditions with the production of ∼80 mM H2 O2 (electrolyte-free) and a faradaic efficiency of ∼90%, which is the highest concentration of pure H2 O2 obtained using PEC systems. This study successfully demonstrates the proof-of-concept that might enable the production of a concentrated pure (electrolyte-free) aqueous solution of H2 O2 using sunlight, water, and dioxygen only.